2009
DOI: 10.1111/j.1526-4637.2009.00657.x
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study Investigating the Effects of Fast Left Prefrontal rTMS on Chronic Neuropathic Pain

Abstract: Objective Stimulating the human cortex using transcranial magnetic stimulation (TMS) temporarily reduces clinical and experimental pain, however, it is unclear which cortical targets are the most effective. The motor cortex has been a popular target for managing neuropathic pain, while the prefrontal cortex has been investigated for an array of nociceptive pain conditions. It is unclear whether the motor cortex is the only effective cortical target for managing neuropathic pain, and no published studies to dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
54
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(61 citation statements)
references
References 51 publications
5
54
0
2
Order By: Relevance
“…24,27 The present study is the first to our knowledge to show that tDCS may be able to produce analgesic effects similar to that of those studies and the first to use either type of brain stimulation to decrease periprocedural pain in endoscopy. The optimal cortical targets for stimulation are not wellestablished.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…24,27 The present study is the first to our knowledge to show that tDCS may be able to produce analgesic effects similar to that of those studies and the first to use either type of brain stimulation to decrease periprocedural pain in endoscopy. The optimal cortical targets for stimulation are not wellestablished.…”
Section: Discussionsupporting
confidence: 66%
“…24,27 The same may not necessarily hold true for tDCS. It is possible that mood-modulating effects of prefrontal tDCS in the present study drive changes in pain appraisal and pain behaviors that confound our results.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Nociceptive cutaneous heat stimuli were applied using a TSA-II Neurosensory Analyzer (Medoc, Durham, NC) using a 3 · 3 cm thermode on the volar aspect of distal left forearm. The apparatus is MRI compatible and is frequently used in several pain studies and is seldom associated with adverse events (Borckardt et al, 2009). For thresholding, the participants' skin was permitted to adapt to a temperature of 32°C for some time.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have found beneficial effects of TMS for acute and chronic pain. 4,5 In terms of chronic orofacial pain, there are many subtypes, and some argue that the subtypes differ substantially. 6 Although some studies have shown the efficacy of daily fast rTMS for orofacial pain including atypical facial pain, dental pain, and neuralgia, 4,5 there appear to be no reports on the efficacy of rTMS for BMS.…”
mentioning
confidence: 99%